Coping with the toll of child sexual abuse investigations - Lauran Easton; John Synnott; Dara Mojtahedi; Maria Ioannou (Frontiers in Psychology)
IntroductionThe policing of child sexual abuse (CSA) can have adverse psychological consequences on police personnel. Though some emerging research has shown a negative impact on quality of life, less is known about the coping strategies used by such professionals when working on CSA cases.MethodsThe present study surveyed 68 police personnel involved in the investigation and/safeguarding of CSA about their occupational wellbeing (Compassion Satisfaction, Burnout, Secondary Traumatic Stress, and Depression) and coping strategies to work-related stress.ResultsFindings demonstrated that the majority of respondents reported low to moderate levels of negative occupational wellbeing, however, a considerable minority, specifically those using venting, self-blame and behavioural disengagement as coping strategies, reported severe negative mental wellbeing.DiscussionThe findings highlight the need for policing organisations to support personnel in identifying and using healthy coping approaches that do not exacerbate the effects workplace stress. The authors identify the need for future research to identify specific problem-focussed approaches that are effective in mitigating the effects of workplace stress on mental wellbeing.